Occupational stress and turnover intentions in employees of the Portuguese tax and customs authority: Mediating effect of burnout and moderating effect of motivation - Mariana Freitas; Ana Moreira; Fernando Ramos (Administrative Sciences, 2023)
The main objective of this study was to study the effect of occupational stress on turnover intentions, as well as determine whether this relationship is mediated by burnout levels and moderated by motivation. The sample size of this study consisted of 603 participants, all employees of the Portuguese Tax and Customs Authority, which is part of the Ministry of Finance and belongs to the Direct State Administration. The results indicate that occupational stress (with managers, career and pay, and overwork) has a positive and significant effect on turnover intentions and that this relationship is mediated by burnout. Motivation (intrinsic and identified) has a negative and significant effect on turnover intentions. Intrinsic motivation moderates the relationship between occupational stress (with managers, colleagues, career and pay, and family problems) and turnover intentions. These results indicate that among the dimensions of occupational stress, the most critical are the stress caused by managers, work overload, and career and pay. These are factors that the Direct State Administration should be concerned with to reduce employees' stress levels, as well as their turnover intentions.
Keywords: 350; burnout; motivation; occupational stress; quantitative study; turnover intentions